The Reproductive Ability Indicators and Their Influence on the Cows’ Milk Yield - Димчук, А. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The aim of research was to study an indicators reproductive cows’ ability of Podilian mill type of the Ukrainian black and white dairy cattle and their impact on expectations. Was studied a milk yield of the 305 days of the first lactation; age of the first calving; between parturition period; the length of service period and the coefficient reproductive ability the Ukrainian black and white dairy cattle (the last 10 years; n = 534). It is established that milk yield; to some extent; dependents on the age of the first calving; between parturition period; the length of service period and the coefficient reproductive ability. The milk yield for the first cows’ lactation is increased with increasing duration of service period and the period between I and II calving and with decreasing age of the first calving and reproductive ability factor. The age of the first cows’ calving is not less than 30 months. The relatively late age of first calving cows in this sector is caused by the growth characteristics; development and the body weight of heifers at first insemination; which is not less than 400 kg. It is proved the possibility of increasing the milk yield firstborn in their younger age calving and at the same time the simultaneous reduction of non-productive period growth. It is recommended to provide a sufficiently high level of growing heifers; especially during the intense puberty and reduce the age of first calving; which will increase the output of calves per 100 cows; to reduce the cost of cultivation and will reduce the generation interval between generations; which will increase the rate of genetic progress and more productive longevity of animals.